EFFECTIVE MEANS OF FORMATION OF SOCIO-CULTURAL COMPETENCE OF JUNIOR SCHOOL CHILDREN - Blyznyuk, Tetyana; Kachak, Tetiana (Mountain School of Ukrainian Carpaty, 2021)
The article reveals the essence and structural components of socio-cultural competence of junior schoolchildren. It is noted that socio-cultural competence is necessary in order to develop the child's worldview, self-perception as a representative of a certain nation, the bearer of national culture; self-awareness as a member of society and a citizen of one's country who is responsible for its future. The means of formation of socio-cultural competence of junior schoolchildren at the lessons of the language-literary cycle are analyzed. The efficiency and expediency of using integrated lessons, roleplaying games for this purpose in primary school are substantiated. Work with authentic texts in the process of learning a foreign language; intercultural interaction; games, staging and dramatization; reproductive, constructive and creative tasks on the basis of the read texts of sociocultural subjects are stated in the article. The relevance of using digital tools as a means of forming socio-cultural competence of students in the modern educational process (programs for creating and watching videos, multimedia presentations, slide shows, didactic and educational content, search engines, google-forms, services for distance learning, testing, etc.) are described.